Cardiovascular risk factors among Chamorros - Wu Phillis L; Nguyen Victoria; Chiem Binh; Ko Celine M; Cruz Lee; Sadler Georgia (BMC, 2006)
Abstract Background Little is known regarding the cardiovascular disease risk factors among Chamorros residing in the United States. Methods The Chamorro Directory International and the CDC's Behavioral Risk Factor Surveillance System Questionnaire (BRFSS) were used to assess the health related practices and needs of a random sample of 228 Chamorros. Results Inactivity, hypertension, elevated cholesterol and diabetes mellitus were more prevalent in this Chamorro sample compared to the US average. Participants who were 50-and-older or unemployed were more likely to report hypertension, diabetes and inactivity, but they were also more likely to consume more fruits and vegetables than their younger and employed counterparts. Women were more likely to report hypertension and diabetes, whereas men were more likely to have elevated BMI and to have never had their blood cholesterol checked. Conclusion The study provides data that will help healthcare providers, public health workers and community leaders identify where to focus their health improvement efforts for Chamorros and create culturally competent programs to promote health in this community.